Could anyone direct me on how to solve these? Im stuck. (n-1 are subscripts)
An=2An-1 -3, a0 = -1
An=(n+1)An-1, a0=2
An=2nAn-1, a0=3
An=-An-1 + n - 1, a0 = 7
Hello, vexiked!
I'll walk through the first one.
Could anyone direct me on how to solve these?
We conjecture that is of the form: . , an exponential expression.
Subtract [2] - [1]: .
Divide by
. . Hence, the function has: .
Form a linear combination of the two roots: .
. . and we have: .
Use the first two terms of the sequence:
. .
Subtract [4] - [3]: .
Substitute into [3]: .
Therefore: .